2016
DOI: 10.1293/tox.2015-0082
|View full text |Cite
|
Sign up to set email alerts
|

Transient effects of empty liposomes on hepatic macrophage populations in rats

Abstract: Liposomes have been used as a vehicle for encapsulating chemicals or toxins in toxicological studies. We investigated the transient effects of empty liposomes on hepatic macrophages by applying a single intravenous injection at a dose of 10 ml/kg body weight in 6-week-old male F344 rats. One day after injection, the numbers of hepatic macrophages reacting to CD163, CD68, Iba-1, MHC class II, Gal-3 and CD204 were significantly increased in liposome-treated rats. CD163+ Kupffer cells and CD68+ macrophages with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…No differences in TUNEL + islet cells or pHH3 + islet cells were observed between groups ( Figures S4C and S4D). Effects of PBS-liposomes were consistent with a previously described effect of liposomes themselves on macrophage function (Ma et al, 2011;Pervin et al, 2016), or might have been due to macrophage depletion with PBS-liposomes (Weisser et al, 2011). These data show that islet macrophages help maintain beta-cell insulin secretion.…”
Section: Islet Macrophage Depletion Decreases Igf1 Expression Followisupporting
confidence: 90%
“…No differences in TUNEL + islet cells or pHH3 + islet cells were observed between groups ( Figures S4C and S4D). Effects of PBS-liposomes were consistent with a previously described effect of liposomes themselves on macrophage function (Ma et al, 2011;Pervin et al, 2016), or might have been due to macrophage depletion with PBS-liposomes (Weisser et al, 2011). These data show that islet macrophages help maintain beta-cell insulin secretion.…”
Section: Islet Macrophage Depletion Decreases Igf1 Expression Followisupporting
confidence: 90%
“…It is interesting to note that clodoranete treatment induces hepatic macrophage depletion without histopathological lesions, resulting in increased values of AST and ALT 43) . As mentioned above, AST and ALT values are decreased under hepatic macrophage activation 24,40) . In liver homeostasis, the conditions of hepatic macrophages influence AST and ALT values, suggesting that hepatic macrophages participate in clearance of these hepatic deviation enzymes 17,46) .…”
Section: -2 Influences On Depletion Of Hepatic Macrophages In Homeomentioning
confidence: 70%
“…There would be chemicals capable of activating or inhibiting hepatic macrophage functions as an initial toxicity. Novel pathogenesis may be brought out in relation to hepatic macrophage functions 40,43) . The analysis of macrophage conditions in rat toxicity studies would lead to refinement of hazard characterization.…”
Section: -2 Influences On Depletion Of Hepatic Macrophages In Homeomentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, macrophages including blood monocyte-derived macrophages, tissue resident macrophages (histiocytes/Kupffer cells) and antigen-presenting macrophages (dendritic cells) play important roles in tissue homeostasis and pathological lesion development. We previously showed that administration with empty liposome, which can be ingested by macrophages, activates Kupffer cells in rats; interestingly, the treated rats showed decreased values of serum hepatic deviation enzymes, although there were no observable changes in histological structures 1 . Kupffer cells may be responsible for liver homeostasis.…”
Section: Introductionmentioning
confidence: 90%